The Antihypoxic and Sedative Activity of the Dry extract from Asperula odorata L. - Sergeevna, Iurchenko Nataliia; Vasilevna, IlyinaTatyana; Mihaylovna, Kovaleva Alla; Leonidivna, Toryanik Erica; Aleksandrovna, Kulish Irina (Pharmacognosy Communications)
Introduction: Sweet Woodruff (Asperula odorata L.) is a perennial herb that is spread throughout the territory of Ukraine. This herb is widely used in folk medicine of Ukraine as a sedative medicine at neurosis, neurasthenia, hysteria, depression, applied locally at allergic rash, and it is also used at metritis and colpitis in homeopathy. Materials and methods: The air-dried herb of Asperula odorata was degreased with chloroform and then treated with the mixture of ethyl acetate-alcohol (8:2) to obtain a dry extract. Sedative activity was studied in the “open field” test. The protective effect of dry extract against hypoxia-induced lethality in mice was evaluated by experimental model of asphyctic hypoxia. HPLC analysis was used to identify the phenolic compounds in the dry extract. Results: The dry extract at the dose of 100 mg/kg in the “open field” test caused a significant dose-dependent (p>0.05) decreasing of loco motor activity which has evidenced by potent sedative activity. The dry extract at the dose of 100 mg/kg showed a potent anti-hypoxic activity which has been confirmed by increasing mice lifetime by 34.8% in conditions of model hypoxia. The dry extract reveals a sedative activity on the CNS but it doesn’t have an adverse effect on skeletal muscle tone and coordination. In the dry extract, 16 phenolic compounds have been identified and quantified. Chlorogenic acid and cynarozide are dominant compounds. Conclusion: Our data have provided a rational base for the folkloric use of the dry extract from Sweet Woodruff as a sedative and antihypoxic drug.
Keywords: Antihypoxic activity; dry extract; HPLC; Phenolic compounds; Sedative activity; Sweet woodruff